2001
DOI: 10.25336/p6d88h
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influence, economic security, and the fertility behavior of the Chinese in Canada

Abstract: This study explores interactions of cultural influence and economic insecurity and their effects on the fertility behavior of the Chinese in Canada. The importance of group context on the actions of individuals is measured through data from the PUST of the 1971 and 1991 Canadian Censuses. Contextual analysis and random coefficient models are the major statistical tools employed to achieve the above objectives. The Chinese-Canadians are compared to the British-Canadians, who are used as the reference group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The second dimension of adaptation refers to the importance of cultural heritage in the fertility behavior of migrants. Unique norms and values pertaining to family formation reflect the history and beliefs shared by members of an immigrant group regardless of socio-economic status (Abbasi-Shavazi and McDonald, 2000; Carter, 1998; Hammel, 1990; McQuillan, 2004; Sorenson, 1985, 1988; Tang, 2001; Thapa, 1989). This model predicts higher or lower fertility rates of immigrants than that of the natives at every level of socio-economic status because of continuing adherence to the norms and values of the origin society or low level of cultural adaptation to the host society.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The second dimension of adaptation refers to the importance of cultural heritage in the fertility behavior of migrants. Unique norms and values pertaining to family formation reflect the history and beliefs shared by members of an immigrant group regardless of socio-economic status (Abbasi-Shavazi and McDonald, 2000; Carter, 1998; Hammel, 1990; McQuillan, 2004; Sorenson, 1985, 1988; Tang, 2001; Thapa, 1989). This model predicts higher or lower fertility rates of immigrants than that of the natives at every level of socio-economic status because of continuing adherence to the norms and values of the origin society or low level of cultural adaptation to the host society.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The role of tradition and culture in reproductive decisions and sex preferences are stronger in families belonging to small communities and ethnic minorities, since higher fertility and presence of sons are regarded as factors of power and authority in these communities ( 24 ). According to Félix (2012) and Tong (2001) different ethnic groups demonstrated their sex preference in fertility even after moving, leading to differences in reproductive behavior toward their new hosts ( 26 , 27 ). Interactions of cultural influence and economic insecurity affect the reproductive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of these findings showed that the norms and cultural beliefs of people with respect to fertility, has a great impact on reproductive behavior of these people. This influence effectively shows the effect of original culture on fertility, demanding the compensation of lower fertility after the initial immigration phase ( 27 ). Another reason for stronger sex preferences in Turkman society relative to other ethnic groups is related to the type of employment, traditional economy and residence of Turkman people.…”
Section: Discussionmentioning
confidence: 99%